Performance assessment of swarm-assisted mean error estimation-based fault detection technique for transmission line protection. (October 2018) - Prasad, Ch.D.; Nayak, Paresh Kumar
Abstract: In this paper, a fast and computationally efficient fault detection algorithm is proposed for power transmission network protection using mean error estimation technique. In order to avoid false detection, instead of adopting the traditional trial and error-based approach, particle swarm optimization-assisted optimal threshold setting method is introduced in this paper. Performance of the proposed fault detection technique is tested for numerous fault and non-fault events generated on a two-bus test power system through MATLAB/SIMULINK software. The observations on results clearly show that using the proposed method even critical faults can be detected securely within a quarter cycle of the 50 Hz power system. The comparative assessment with two existing methods confirms the effectiveness of the proposed scheme.